Influence of Nitrogen Levels and Weed Management Practices on Yield and Quality of Forage Pearl Millet (Pennisetum glaucum L.) - Choudhary, Sunita; Chopra, Neelam K.; Chopra, Nisha K.; Singh, Magan; Kumar, Rakesh; Kushwaha, Manish (Indian Journal of Animal Nutrition, 2017)
A field experiment was conducted using split plot design consisting of 4 nitrogen levels (0, 50, 100 and 150 kg N/ha) and 6 weed management practices (W1- pendimethalin application @ 1.0 kg a.i./ha pre-emergence (PE) + 1 hand weeding (HW) at 25 DAS, W2- atrazine application @ 0.75 kg a.i./ha PE + 1 HW at 25 DAS,W3- pendimethalin application @ 1.0 kg a.i./ha PE + halosulfuron application @ 67.5 g a.i./ha post emergence (POE) at 25 DAS, W4- atrazine application @ 0.75 kg a.i./ha PE + halosulfuron application @ 67.5 g a.i./ha POEat 25 DAS, weedy check and weed free) with three replications during kharif season of 2015 to evaluate the effect of nitrogen and weed management on yield and quality of forage pearl millet var. HC-20. The plant height (cm), leaves/plant, tillers/plant, green and dry fodder yield/ The CP and EE contents increased (P